Developing management skills : techniques for improving learning & performance - Dale, Margaret (London : Kogan Page, 1998)
The author focuses on the way in which job-related and on the job activities can be used as opportunities for learning, with the intention of providing managers with the ability to devise approaches to suit their own situations and staff. Second revised edtion. Aimed at middle management, HRM professionals, MBA and DMS students.
Keywords: Management -- Study and teaching; Executives -- Training of; Employees -- Training of